Supramolecular Nested Microbeads as Building Blocks for Macroscopic Self‐Healing Scaffolds. Issue 12 (21st February 2018) - Yu, Ziyi; Liu, Ji; Tan, Cindy Soo Yun; Scherman, Oren A.; Abell, Chris
Abstract: The ability to construct self‐healing scaffolds that are injectable and capable of forming a designed morphology offers the possibility to engineer sustainable materials. Herein, we introduce supramolecular nested microbeads that can be used as building blocks to construct macroscopic self‐healing scaffolds. The core–shell microbeads remain in an "inert" state owing to the isolation of a pair of complementary polymers in a form that can be stored as an aqueous suspension. An annealing process after injection effectively induces the re‐construction of the microbead units, leading to supramolecular gelation in a preconfigured shape. The resulting macroscopic scaffold is dynamically stable, displaying self‐recovery in a self‐healing electronic conductor. This strategy of using the supramolecular assembled nested microbeads as building blocks represents an alternative to injectable hydrogel systems, and shows promise in the field of structural biomaterials and flexible electronics. Abstract : Self‐healable scaffolds : Supramolecular nested microbeads that are capable of isolating a pair of complementary polymers were developed for the construction of macroscopic self‐healing scaffolds. This protocol promotes the polymer flowability for injection while retaining self‐healing behaviour on account of the dynamic molecular interactions.